Aqueous cinnamon extract ameliorates bowel dysfunction and enteric 5-HT synthesis in IBS rats - Yu, Lijuan; Huang, Chunhua; Yang, Wei; Ren, Zhenxing; Li, Lifeng; Cheng, Huiyuan; Lin, Chengyuan; Zhai, Lixiang; Ning, Ziwan; Wong, Hoileong Xavier; Han, Quanbin; Jia, Wei; et al. (Frontiers in Pharmacology, 2023)
Cinnamon protects against irritable bowel syndrome with diarrhea (IBS-D) in humans, but its efficacy and underlying mechanism of action remain poorly understood. Maternally separated (MS) IBS-D rat model and 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced post-inflammatory IBS-D rat model are characterized by visceral hyperalgesia and diarrhea. This study used the two models to evaluate the effect of cinnamon extract (CE) on bowel symptoms. The MS rat model was also used to explore its underlying anti-IBS mechanism. CE reduced defecation frequency and visceral hyperalgesia in MS rats in a dose-dependent manner and effectively improved visceral hyperalgesia in TNBS rats. The efficacy of CE was comparable to the positive drug serotonin receptor 3 (5-HT3) selective antagonist, Ramosetron. Excessive 5-HT, a well-known pathogenic factor for IBS, in the colon and circulation of IBS rats was reduced after CE intervention. Both, gene and protein levels of the colonic 5-HT synthetase, Tryptophan Hydroxylase 1 (Tph1), were also decreased in CE-treated IBS rats. In addition, a luciferase assay revealed that CE and its major components, catechin, procyanidin B1/2, cinnamic acid, and cinnamyl alcohol, significantly inhibited Tph1 transcription activity in vitro. These findings illustrated that aqueous CE partially attenuated bowel symptoms in IBS models by directly inhibiting Tph1 expression and controlling 5-HT synthesis. This provides a scientific viewpoint for the use of cinnamon as a folk medication to treat IBS.